Fish stocking for recreational angling is culpable for the poor condition of many English lakes designated for conservation purposes. Issue 1 (2nd January 2022) - Skeate, Eleanor R.; Perrow, Martin R.; Tomlinson, Mark L.; Madgwick, Genevieve; Harwood, Andrew J. P.; Ottewell, David; Berridge, Richard; Winfield, Ian J.
ABSTRACT: Contemporary surveys and analysis of previous data identified negative effects of fish stocking for recreational angling in 87% of 23 English lakes (0.2–26 ha and 1–11.9 m mean depth) protected for nature conservation as Sites of Special Scientific Interest (SSSI). All sites except one were in unfavourable condition, with 92% failing to meet targets for characteristic macrophyte species. No lake was judged to have a natural fish community, and 96% had been subjected to fish stocking. The naturalised alien common carp ( Cyprinus carpio ) was the most widely introduced (87%). The presence of further alien species indicated illegal activity. A combination of estimates from surveys and angler records suggested carp comprised 53% of overall fish biomass density, with values up to 1164 kg ha −1 in individual lakes. Successful recruitment of carp, attributed to a warming climate, was recorded in 44% of the lakes in which it occurred. Consideration of fish impacts on lake ecology from the literature concluded that management of fish stocks, through biomanipulation, was required. The efficacy of biomanipulation was demonstrated by removal of fish from a large exclosure (29% of area) in one study lake and a resultant favourable response of water transparency and macrophyte growth. In the wider SSSI lakes series, we concluded that the retention of carp in any lake was an unacceptable risk to restoration of favourable condition, as were damaging angling practices. A ban on fish stocking in SSSI lakes is recommended, unless fish are introduced to restore natural communities.